Brain Structural Bases of Tendency to Forgive: evidence from a young adults sample using voxel-based morphometry - Haijiang Li (Nature Portfolio, 2017)
Abstract Tendency to forgive refers to one’s global dispositional level of forgiveness across situations and relationships. Brain imaging studies examined activation patterns underlying forgiving response, yet focal differences in brain structures related to tendency to forgive have never been investigated. In this study, voxel-based morphometry was used to investigate relations between gray matter/white matter volume (GMV/WMV) and individual differences in tendency to forgive in a large young sample. Participants were 199 young students (60 men) who completed the tendency to forgive scale (TTF) and underwent an anatomical magnetic resonance imaging scan. Results showed that higher TTF scores were associated with larger GMV in the regions of dorsolateral prefrontal cortex, and smaller GMV in the regions of the right insular cortex and inferior frontal gyrus (IFG). Moreover, higher TTF scores were also related to smaller WMV in the regions of the left IFG. Together, these findings suggest structural variations for individual differences in the tendency to forgive, distributed across different brain regions associated with empathic response and cognitive control.